2001
DOI: 10.2528/pier00112005
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Luebbers' and Maliuzhinets' Wedge Diffraction Coefficients in Urban Channel Modelling

Abstract: Abstract-Luebbers' and Maliuzhinets' solutions for diffraction by a lossy wedge are compared in order to model the urban propagation channel. Derivation, validity criteria and accuracy of impedance boundary conditions (IBCs)-as a main approximation embedded in the Maliuzhinets' solution-are discussed. A modified (a slightly improved) Luebbers diffraction coefficient is proposed. The Uniform Theory of Diffraction (UTD) Maliuzhinets diffraction coefficient is given in a structured form that might facilitate its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 16 publications
1
31
0
Order By: Relevance
“…Alternatively, the MZ is another option for solving the configuration with the thin material discontinuities. All of these solutions [10][11][12][13][14][15] are based on the MZ method. Unlike W-H and MZ solutions, the solution developed in this work recover the proper local plane wave Fresnel reflection and transmission coefficients (FRTCs), and surface wave constants, respectively, for the actual material, and they also allow the material to be both double positive (DPS) or double negative (DNG).…”
Section: (A)mentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, the MZ is another option for solving the configuration with the thin material discontinuities. All of these solutions [10][11][12][13][14][15] are based on the MZ method. Unlike W-H and MZ solutions, the solution developed in this work recover the proper local plane wave Fresnel reflection and transmission coefficients (FRTCs), and surface wave constants, respectively, for the actual material, and they also allow the material to be both double positive (DPS) or double negative (DNG).…”
Section: (A)mentioning
confidence: 99%
“…It is necessary to introduce this unknown constant in this 3-D situation to suppress the nonphysical poles, which may occur in the tangential field components E z and H z for the skew incidence case. In addition, this unknown constant W will make the 3-D PWS integral in (13) to recover the 2-D PWS integral when β o → π/2 or at normal incidence. This unknown constant W will be determined later.…”
Section: Ansatz For the Obliquely Incident Plane Wave Illumination Camentioning
confidence: 99%
“…A perturbation technique is developed to determine an approximate field solution. Furthermore [3], examines the question of the choice between two kinds of diffraction coefficients used to model urban channels. Scattering by wedge structures is analyzed to explain the motivation of the choice.…”
Section: Introductionmentioning
confidence: 99%
“…Here, Fresnel reflection coefficient, , are calculated with angle and as per angular definition of Aidi and Lavergnat [9] given as…”
Section: Available Heuristic Diffraction Coefficientmentioning
confidence: 99%
“…However, these coefficients were neither reciprocal nor symmetrical. In [7], a reciprocal heuristic coefficient was defined that used the angle definition proposed by Aidi et al [9] and showed good agreement over other available coefficients. However, this showed the reciprocity property only when the transmitter (Tx) and the receiver (Rx) were either side of the wedge.…”
Section: Introductionmentioning
confidence: 99%